Detection of KatG Mutation in MDR Mycobacterium Tuberculosis Isolates by PCR-RFLP and DNA Sequencing - Ilyas, Muhammad; Niaz, Falak; Ishaq, Rafaqat; Rafiullah; Khanum, Azra (Bangladesh Journal of Medical Science, 2023)
Objective: Tuberculosis (TB) is among the widespread and rapidly growing infections in the world. Furthermore, TB is one of the major public health problems in Pakistan as every year 48,000 Pakistani dies due to this infection. Pakistan ranks fifth among high burden countries worldwide. As the TB has become most threatening because of the epidemics of human immune deficiency virus (HIV), Covid-19 and the emergence of multi-drug resistance (MDR) strains of Mycobacterium tuberculosis (M. tb). This study was aimed to understand the genetic mechanism of drug resistance in local TB isolates. Methodology: For the genetic studies of INH resistance, KatG (encoding catalase peroxidase) hotspot region was amplified through PCR followed by RFLP and sequencing. Results: The study of PCR-RFLP showed that forty-five out eighty INH resistant M. tb strains had mutations in KatG (codon 315) which is 56.2% of all cases. Sequencing results revealed that this is substitution mutation; AGC to ACC (Ser315Thr). Conclusion: It may be concluded that majority of INH resistance is due to the mutation in the codon 315 of KatG in local isolates. Furthermore, PCR-RFLP technique could be considered as a reliable method for the early detection of KatG mutations in MDR-TB. Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page : 804-808